pH-Responsive Near Infrared Light Triggered Hydroxyapatite Nanoparticles for Targeted Photothermal Cancer Therapy - Loganathan Palanikumar; Faten Mansoor Yasin; Munkhjargal, Itgel; Boitet, Maylis; Ali, Liaqat; Muhammed Shiraz Ali; Straubinger, Rainer; Francisco Nicolas Barrera; Magzoub, Mazin (bioRxiv, 2025)
Photothermal therapy (PTT) has emerged as an effective cancer treatment strategy, which utilizes photothermal agents that accumulate at tumor sites and induce localized hyperthermia when irradiated. Near-infrared II (NIR II) fluorophores, such as the polymethine cyanine-based photothermal dye IR1061, exhibit higher temporal resolution and better tissue penetration, thereby making them promising candidates for PTT. However, challenges such as the low water solubility and in vivo short circulation times of these dyes limit their biological applications. To address these issues, we have developed a biocompatible and biodegradable delivery system in which IR1061 is encapsulated within lipid-coated hydroxyapatite nanoparticles (LHAPNIRs). The lipid shell is composed of DPPC/cholesterol/DSPE-PEG to retain the encapsulated dye and prevent serum protein adsorption and macrophage recognition, which would otherwise that hinder tumor targeting. Finally, the coat is functionalized with an acidity-triggered rational membrane (ATRAM) peptide for efficient and specific internalization into tumor cells in the mildly acidic microenvironment characteristic of tumors. The nanoparticles facilitated real-time thermal imaging and showed potent NIR-light triggered anticancer activity in vitro and in vivo, with no noticeable toxicity to healthy tissue. Our results demonstrate that ATRAM-LHAPNIRs (ALHAPNIRs) combine potent PTT and robust diagnostic imaging capabilities.Competing Interest StatementThe authors have declared no competing interest.